Optical characteristics of Al₂O₃ oxide coatings on copper mirrors made by diamond microgrinding - Odarich, V.A.; Poperenko, L.V.; Staschuk, V.S.; Filipov, Y.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Ellipsomety examination of dielectric sheetings and measured of reflection spectrum at normal incidence there carried out. A film of Al₂O₃ on a surface of copper mirrors of a diamond microgrinding was deposited. The thickness and index of refraction of coatings are determined.